2019
DOI: 10.1097/mph.0000000000001706
|View full text |Cite
|
Sign up to set email alerts
|

Severe, Fatal Methotrexate-related Neurotoxicity in 2 Adolescent Patients With ALL

Abstract: Neurotoxicity is a well-documented adverse effect of methotrexate in the treatment of pediatric cancers. The spectrum of symptoms is broad, can include stroke-like episodes and seizures, and classically resolves within days. The majority of patients tolerate subsequent doses without recurrence of symptoms. The population of patients who experience persistent and irreversible neurological symptoms is poorly described, with the existing literature suggestive of a relationship with radiation therapy. The authors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…As stated, this is typically transient, and most patients can receive subsequent MTX without recurrence of symptoms. Nevertheless, there are reports of very rare cases of poor neurologic outcomes and even fatalities with progressive encephalopathy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…As stated, this is typically transient, and most patients can receive subsequent MTX without recurrence of symptoms. Nevertheless, there are reports of very rare cases of poor neurologic outcomes and even fatalities with progressive encephalopathy [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that giving folinic acid in the first 24-36 hours after initiating MTX therapy can prevent neurotoxicity [17]. Secondly, after the onset of the neurological symptoms, Dextromethorphan, an N-methyl-D-aspartate receptor antagonist, and aminophylline, an adenosine receptor antagonist, have been helpful in the management of MTX-neurotoxicity [1], [11], [18].…”
Section: Discussionmentioning
confidence: 99%
“…However, cau tion is warranted as there are case reports of patients with poor neu ro logic out comes and rare fatal i ties after repeated epi sodes of meth o trex ate neu ro tox ic ity. 9,20 In these uncom mon sce nar ios, par tic u larly when patients do not make a full recov ery in the expected time frame or have recur rent severe meth o trex ate neu ro tox ic ity, com ple tion of CNS-directed ther apy with alter nate agents would require an indi vid u al ized approach based on the patient's risk of CNS relapse.…”
Section: Recurrence Of Meth O Trex Ate Neu Ro Tox Ic Itymentioning
confidence: 99%